Volumetric and Rutting Analysis on Degradation of Aggregate and Asphalt Reclaimed Asphalt Pavement - Tambunan, Hermon Frederik; Hadiwardoyo, Sigit Pranowo; Sumabrata, Raden Jachrizal; Lumingkewas, Riana Herlina (Engineering, Technology & Applied Science Research, 2025)
The performance of a hot asphalt mixture as a road surface layer is subject to deterioration due to the effects of traffic loads and weather conditions. The process of asphalt aging is characterized by a decline in physical properties and alterations in aggregate composition. To maintain the integrity of the road surface, the surface layer is periodically removed and recycled. This study aims to simulate the process of aggregate and asphalt degradation as an asphalt aging process. The study proposes a model with five levels of asphalt physical property decline and four levels of Coarse Aggregate (CA), arranged into 20 variations. The analysis results indicate that a decrease in the percentage of CA reduces stability and increases air cavities, while an increase in asphalt penetration on specific CAs increases cavity volume and stability. The correlation test results demonstrate that the mixture with optimal CA strengthens resistance to deformation, especially at low-temperature conditions. However, at temperatures of 40 °C and 55 °C, the initial deformation rate increases sharply. The degraded mixture exhibits a decrease in deformation resistance at high temperatures. The findings of this study can be used to ascertain the optimization of the residual value of the performance of asphalt concrete mixtures for recycling processes involving reconditioning aggregate and asphalt.